KLON-KLON KENTANG TRANSGENIK HASIL PERSILANGAN TERSELEKSI TAHAN TERHADAP PENYAKIT HAWAR DAUN PHYTOPHTHORA INFESTANS TANPA PENYEMPROTAN FUNGISIDA DI EMPAT LAPANGAN UJI TERBATAS - Ambarwati, Alberta Dinar, Kusmana; Listanto, Edy (Perhimpunan Biologi Indonesia, 2015)
ABSTRACTThe use of resistant varieties is an appropriate alternative in controlling the late blight, a major diseases on potato, caused by the fungus Phytophthora infestans. The development of late blight resistant potato was done through hybridization between non-transgenic Atlantic or Granola with RB transgenic Katahdin SP904 and SP951. The hybrid clones which have been positively contained the RB gene were evaluated for the resistance to P. infestans in four Confined Field Trials (CFTs) i.e. Pasir Sarongge (2008), Lembang (2009-2010), Pangalengan (2010-2011) and Banjarnegara (2011-2012). There are twelve selected hybrid clones which were resistant to P. infestans both in each location of CFT or in four locations were obtained. These clones consist of five clones from crosses of Atlantic and trangenic Katahdin SP951 (B35, B169, B163, B11, B162) and seven clones from crosses of Granola and transgenic Katahdin SP951 (D76, D12, D25, D48, D38, D37, D15). The selected hybrid clones showed resistance to P. infestans until 14 to 18 days after infection or about 40 to 45 days after planting, in the absence of fungicide spraying. The hybrid clones had a resistance score varied from 7,65 to 8,23 and were significantly different from the parents Atlantic and Granola, with a resistance score of 3,6 and 3,45, respectively. This was also supported by AUDPC values, which showed that AUDPC of the hybrid clones were in the range between Atlantic or Granola and transgewnic Katahdin SP951. This indicate that the resistance level of the hybrid clones is in the range between susceptible and resistant check. The resistant hybrid clones are valuable genetic resources for late blight resistance breeding programs, particularly in reducing the frequency of fungicide applications. Keywords : transgenic potato, hybrid clones, Phytophthora infestans, confined field trial